Strategy for Digital Competence Development of Economics, Business and Accounting Lecturers : Human Capital Theory Review - Kardiyem Kardiyem; Bandi Bandi; Kristiani Kristiani; Fery Setyowibowo (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze strategies universities can use to develop appropriate digital competencies for economics, business, and accounting lecturers and also provides an overview of the framework. This study employed a narrative literature review method with a qualitative approach consisting of several steps: compilation, tabulation, research result comparison, and summarization. The literature sources were the related articles dated within the last 15 years (2009-2023) acquired from reputable international journal sites (Emerald, Elsevier, Springer, Routledge, and MDPI). Content analysis technique was used to analyze the data. The results of this study showed that some existing frameworks in the world rarely include digital ethics dimensions. The digital competency framework for accounting lecturers consists of several elements, including the capacity to use digital sources, assessments, teaching and learning processes, as well as empowering digital literacy for students, small and medium-sized enterprises' people (UMKM), and also now BUMDES' people as well. Strategies that can be carried out by universities in developing human capital for lecturers of economics, business, and accounting in digital competence are by approaching the human capital component through university policies, providing organizational infrastructure and culture (Organization Climate), strategic leadership, or currently being able to adopt digital leadership (leadership component), and various training according to the needs and areas of expertise of lecturers.